APPLICATION OF AUGMENTED REALITY IN E-COMMERCE - Rundāne, Guna; Litavniece, Lienīte (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2021)
The problem of research is still relatively low usage of augmented reality mobile applications in e-commerce, despite it’s advantages and opportunities to increase competitiveness. The aim of the research is to find out and explore the benefits of augmented reality in e-commerce. The paper discusses the definition of augmented reality, it’s advantages and looks through most succesfull mobile applications in e-commerce containing augmented reality. The author includes a case study from a very popular app “Makeup Genius” and examines the basis for its success. The most popular augmented reality apps allow customers to virtually try on products saving time by not having to go to a physical store. Several sources point out that the main advantage of augmented reality is greater consumer interaction with the application, which as a result creates a pleasant experience for the customer.